Design and development of blow mould using machining optimization parameters - K., Kadirgama; M. M., Noor; M. M., Rahman; N. M. Zuki, N. M.; M. R. M., Rejab; B., Mohammad (2008)
This paper is concerned on the optimization of the surface roughness when milling mould aluminium alloys (AA6061-T6) with carbide coated inserts. Optimization of the milling is very useful to reduce cost and time for machining mould. The approach is based on Response Surface Method (RSM). In this work, the objectives were to find the optimized parameters and find out the most dominant variables (cutting speed, federate, axial depth and radial depth).The optimized value has been used to develop a blow mould. The first order model indicates that the feedrate is the most significant factors effecting surface roughness and cutting force.